The use of past assessments as a deductive learning tool? Perceptions of students at a South African university - Ontong, J.M.; Bruwer, A. (South African Journal of Higher Education, 2020)
Promoting critical thinking skills in the higher education setting is noted as a key skill required by students. Using a questionnaire approach, this study examined whether first-year students perceived the use of past assessments in preparation for upcoming assessments as a deductive learning tool and used them solely as a study aid and predictor at a South African university, with the focus on the deductive and conductive learnings styles, with specific reference to whether students perceive the past assessments to be used as tools to indicate specifically what will be assessed in terms of historical frequency. The findings suggest that students utilise past assessments as a deductive tool in order to predict future areas that will be assessed, as well as certain characteristics, such as the level of difficulty of question papers. The authors argue that when past assessments are used as a deductive “predictor” of future assessment, this then potentially acts as an inhibitor of developing critical thinking skills. The findings therefore, although acknowledging the value added in terms of higher education students of the revision and practising of past assessments, highlight that assessors in higher education need to be conscious that the use of past assessments as a “predictor” through the repetitive nature of the items being assessed may result in students who are able to pass assessments but who are unable to necessarily demonstrate critical thinking skills as required by module outcomes. The findings of this study therefore present various streams of areas for future research into the better understanding of how past assessments can be used in order to promote critical thinking within higher education modules.